Tine de Moor’s ‘Silent Revolution’. Reconsidering her theoretical framework for explaining the emergence of institutions for collective management of resources - Curtis, D.R. (Igitur, 2013)
Tine De Moor has developed a bold and robust scholarly framework for explaining the emergence of institutions for 'corporate collective action' in her 'Silent Revolution' article of 2008; the significance of which may serve to be the foundation of a research agenda on the commons for years to come. However, as revealed in this review piece, there are some fundamental flaws in the framework, which need to be ironed out first. There remains a problem with causality – in particular, no logical connection in the framework between the 'conditions necessary to make collective action possible' and the 'reasons to opt for collective action'. In summary, this review suggests De Moor's framework is an important step forward for those researching the commons, though it needs to be modified to become more receptive to the socio-political configurations that gave each pre-industrial society its character.
Keywords: Sociale geografie en planologie; Economie; De Moor; Silent Revolution; commons; socio-political structures